Diseño de envases y embalajes para productos agroindustriales de la comunidad de Sarapamba Chuichun - Guamán Cazho, Gladys Lucia (2022)
This research project was carried out in the Sarapamba Chuichun community of the El Tambo canton, Cañar province; in this community, they are dedicated to elaborating agroindustrial products. However, there is no history of a study on the application of containers and packaging for the products they manufacture. Therefore, an analysis is required to improve and increase the rotation of these products in the market. It is identified that primary and secondary packaging is required; therefore, for the preparation of new packaging, relevant aspects of the design are considered, such as the case of the use of a harmonic composition based on modular systems that organize the informative and normative elements established. For the elaboration of the final packaging, the basic, stacking, and communicational functions to be fulfilled are considered in order to make a correct selection of materials and technology. Robert Scott's design methodology is defined theoretical foundation and application of instruments that provide relevant data to determine the fundamental characteristics of the design and obtain an aesthetic and functional product in order to guarantee an increase in the rotation of agro-industrial products in the market.